PENGARUH JIWA KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA YANG BERLOKASI DI DESTINASI AIR TERJUN SIPISO PISO - Rosanta Rista Br Tanggang; Menanti Sembiring; Benni Purba (Jurnal Ekonomi dan Manajemen, 2026)
This study aims to determine the effect of entrepreneurial spirit on business success among business actors located in the Sipiso-Piso Waterfall tourist destination. The research employed a quantitative approach with data collected through questionnaires distributed to business owners. The sample consisted of 35 respondents selected using a saturated sampling technique. Data were analyzed using validity tests, reliability tests, simple linear regression analysis, t-tests, and the coefficient of determination (R²) with the assistance of SPSS version 22. The results indicated that all research instruments were valid and reliable, with Cronbach’s Alpha values of 0.946 for entrepreneurial spirit and 0.870 for business success. The findings revealed that entrepreneurial spirit has a positive and significant effect on business success. The regression analysis showed that an increase in entrepreneurial spirit contributes to higher levels of business success. Furthermore, the t-test results demonstrated a significance value below 0.05, confirming the positive relationship between the variables. The coefficient of determination (R²) value of 0.822 indicates that entrepreneurial spirit explains 82.2% of the variation in business success, while the remaining 17.8% is influenced by other factors not examined in this study.